How to prepare for the TOEFL essay : test of English as a foreign language - Lougheed, Lin, 1946-; Lougheed, Lin, 1946- (Hauppauge, N.Y. : Barron's Educational Series, 2004)
Includes your blueprint for test success, your private tutor, personal instruction for a better essay, and more.
At head of title: Barron's.
Rev. ed. of: Barron's how to prepare for the computer-based TOEFL essay. 1st ed. 2000.
Keywords: English language -- Textbooks for foreign speakers; Test of English as a Foreign Language -- Study guides; English language -- Examinations -- Study guides